An overview of visualization and visual analytics applications in water resources management. (July 2022) - Xu, Haowen; Berres, Andy; Liu, Yan; Allen-Dumas, Melissa R.; Sanyal, Jibonananda
Abstract: Recent advances in information, communication, and environmental monitoring technologies have increased the availability, spatiotemporal resolution, and quality of water-related data, thereby leading to the emergence of many innovative big data applications. Among these applications, visualization and visual analytics, also known as the visual computing techniques, empower the synergy of computational methods (e.g., machine learning and statistical models) with human reasoning to improve the understanding and solution toward complex science and engineering problems. These approaches are frequently integrated with geographic information systems and cyberinfrastructure to provide new opportunities and methods for enhancing water resources management. In this paper, we present a comprehensive review of recent hydroinformatics applications that employ visual computing techniques to (1) support complex data-driven research problems, and (2) support the communication and decision-makings in the water resources management sector. Then, we conduct a technical review of the state-of-the-art web-based visualization technologies and libraries to share our experiences on developing shareable, adaptive, and interactive visualizations and visual interfaces for water resources management applications. We close with a vision that applies the emerging visual computing technologies and paradigms to develop the next generation of hydroinformatics applications. Highlights: Information and scientific visualization, and visual analytics are often characterized as visual computing techniques. Effective visual computing techniques can facilitate data-driven analysis and decision-supports in environmental research. We provide a comprehensive review of past visual computing applications for water resources management. We discuss cutting-edge web-based visualization technologies to help scientists create effective visual interfaces. We describe visions of emerging visual computing techniques for supporting future water management.